The RAND Health Care Payment and Delivery Simulation Model (PADSIM) Concepts, Methods, and Examples - White, Chapin (RAND Corporation, 2016)
This report describes RAND's Health Care Payment and Delivery Simulation Model (PADSIM), developed to more effectively analyze the impacts of current and future reforms to provider payment policy, such as changes in how much providers are paid for their services and the degree to which payments are determined by the volume of services. PADSIM offers a systematic framework for quantifying such reforms and providers' responses to them.